Two-dimensional model of mesoscale processes in the lower atmosphere with allowance for inhomogeneity of temperature and air humidity - Shvarts, Konstantin Grigorievich; Shvarts, Yulia Anatolievna; Shklyaev, Vladimir Aleksandrovich (Computational Continuum Mechanics, 2015)
A new two-dimensional model of mesoscale processes is used to estimate the influence of temperature and air humidity heterogeneities on the formation of vortex structures in the lower atmosphere. The model has been developed on the basis of the local equilibrium approach by averaging the original three-dimensional equations for mesoscale atmospheric processes across the layer. To close the system of equations, an exact solution of the original problem describing the flow homogeneous with respect to horizontal coordinates is applied. The closure consists in determining the nonlinear terms and the values at the boundaries of velocity, temperature and humidity fields via the averaged field. The solution is obtained for an infinite horizontal rotating layer under the assumption of air incompressibility in the lower atmosphere and linear distribution of the temperature and humidity of the underlying surface. Numerical calculations were performed using a grid method, in which an explicit finite difference scheme is applied to a grid of 200×200 nodes. Computations were carried out for the 40×40 km area in the North-Western part of the city of Perm and its immediate vicinity with account for the underlying surface roughness. It has been found that the vortex structure with a vertical axis of rotation arises at significant horizontal gradients of temperature and humidity in the lower atmosphere. The formation of vortex structures also depends on the configuration of the zones of significant gradients and their location relative to the moving air.